ANALISIS REVETMENT SEBAGAI PERLINDUNGAN TEBING SUNGAI BATANG LEMBANG DALAM UPAYA PENGENDALIAN BANJIR KOTA SOLOK - Imran Syofyan Z (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Solok City as a developing city where there is a natural river that passes through the middle which does not escape from flooding every year. The river located in Solok City is the Batang Lembang river. Rainfall used in hydrological planning are Sumani station, Sukarami station and Danau di Bawah station. The calculation of the maximum discharge used in this plan is the Rational method, the Hasper method and the Nakayasu HSS method. The discharge used is the HSS Nakayasu Q25 method with consideration for the calculation of flood routing using the time parameter, which is every hour. The average width of the existing river is 40 m. The planning river width in this analysis is 45 m and the slope of the revetment is 1:1. The revetment structure is divided into each segment of 20 meters. The cliff protection is made of stone masonry 45 cm thick and the embankment height is 2.5 m. The revetment foundation is planned with a concrete pile foundation with a diameter of 400 mm and a depth of 8 meters. After calculating the revetment analysis, the protection of the Batang Lembang riverbank is safe against landslides and is stable against various forces acting on the building.Keywords: flood discharge, river cross section design, cliff protection.